ANALISIS CIRI KEBAHASAAN DAN EJAAN SISWA KELAS VII SMP N 2 PADANG PANJANG - Oktafiazi, Dina; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTÂ This research aims to describe two things. First describes the feature of text fable students of Class VII SMP Negeri 2 Padang Panjang. Second, describe the spelling in the text fable the text of Class VII SMP Negeri 2 Padang Panjang. This type of research is qualitative research with a descriptive method. This research Data is the use of tasks in the text Fable class VII SMP Negeri 2 Padang Panjang. The data source in this study is fable text written in grade VII students. D SMP Negeri 2 Padang Panjang numbering 30 texts. Data is collected through documentation study methods or document utilization. The data analysis technique is done by five procedures. First, identify common elements of data. Secondly, it identifies the data based on the theory of reference. The identification of the data is done by creating the fable text and spelling characteristics identification format. Third, analyzing the data. Fourth, interpret the data that has been analyzed. Fifth, concludes the data description results by writing a report.Kata Kunci: Analisis, Ciri Kebahasaan dan Ejaan, Teks Fabel